Efektivitas Konseling Ibu Terhadap Perilaku Kadarzi Di Kelurahan Kraton Kecamatan Tegal Barat Kota Tegal - Suprijatmi, Tanti; Sunarto, Sunarto (JURNAL RISET GIZI, 2014)
Background : Kadarzi Program has been implemented since 2003. From the results of monitoring have yet to all be family conscious family nutrition. As for the Kadarzi product in the city of Tegal is 52,83% (76% of target in 2011), while in the West of the Palace Kelurahan Tegal Clinics recently reached 32.4%. In order to change health behavior in particular acquired Kadarzi, the granting of necessary information. Provision of the information would enhance public knowledge about it.Granting information by model pemberdayaan family knowledge, focusing on increased the attitudes and behavior counseling and kie kadarzi through development Conseling is a good interpersonnal communication, because in this model, relation between communicator or counselor and clients is happened. And the kind of research true experiment by providing treatment of Kadarzi counseling on the toddler in kelurahan Tegal Barat next treated as group treat. The control group is mother fives in kelurahan palace which do not get treatment counseling.Objective :The purpose of the study is determined the effectiveness of counseling the mother to behavior Kadarzi in Kelurahan Kraton Kecamatan Tegal Barat. The population of study are 885 family. The samples are needed 37 mother who has toddler. Sample-taking is using propotional simple random sampling technique. Test statistic with Kai quadrat with degree of significance α = 0,05 and counting great effectiveness.Method : This study was designed as an quasi experiment using randomized pretest and posttest Control Group Design. Result : result of analysis shows there is no difference between the counseling Kadarzi before treatment group and cluster of control p value = 0,812. After counseling kadarzi behavior is different between treatment group dan cluster of control p value = 0,004.Conclusion : The effectiveness of counseling is 60 %.